Carbon based copper(II) phthalocyanine catalysts for electrochemical CO₂ reduction : effect of carbon support on electrocatalytic activity - Latiff, Naziah Mohamad (2021)
Carbon-metal hybrid materials have shown promising performance as electrocatalysts for CO₂ reduction. Here, a comparative study of how different carbons supports influence this reaction is presented. The tested carbon supports were graphene oxide, multi-walled carbon nanotubes, carbon black and activated carbon while the metal complex selected was copper(II) phthalocyanine (CuPc). The CuPc supported on carbon nanotubes (CNT) and carbon black were found to give higher faradaic efficiencies (FE) for reduced carbon products, i.e. 66.3% and 81.8%, respectively compared to graphene oxide (0.0%) and activated carbon (12.8%). Amongst various sizes of CNT, long and thin tubes (in the range of 10–30 nm diameter size, 10–30 μm length) demonstrated higher FE (66.3%) relative to shorter and thicker ones (7.4%). Additionally, the novel use of CNT synthesized from post-consumer plastic waste was also explored as a potential carbon support material. It demonstrated comparable performance to commercial CNT in terms of FE (70.4%).